Preliminary study of PAX9 single nucleotide polymorphism (rs8004560) in patients with Class II skeletal base malocclusion contributed by mandibular retrognatism - Mohd Saad, Muhammadazril; Abd Rahman, Nur Amin; Mokhtar@Makhtar, Khairani Idah; Abu Bakar, Noraini; Kharuddin, Azrul Fazwan; Wan Taib, Wan Rohani (Penerbit Universiti Sains Malaysia, 2018)
Polymorphism in PAX9 (rs8004560), a gene responsible for craniofacial and tooth development, is often associated with Class II/Div2 malocclusion. This study aimed to detect the presence of PAX9 SNP (rs8004560) and to determine its genotype and allele distribution in Class II skeletal base malocclusion, contributed by retrognathic mandible, in the local Malaysian population. The association of PAX9 SNP (rs8004560) with Class II skeletal base malocclusion was also determined. A case control study was performed on 30 samples; 15 from Class II skeletal base malocclusion, and 15 from Class I skeletal base subject as control. Cephalometric measurements were performed prior to saliva samples collection. Genomic DNA was extracted from unstimulated saliva of all subjects, and the DNA was amplified using specific primers for marker rs8004560, followed by genotyping by sequencing. SHEsis online software was used to analyse Hardy-Weinberg Equilibrium (HWE) for cases and controls. Allelic and genotypic frequencies were compared between cases and controls. Significant difference in allele frequency was observed within the group whereby G allele was over-represented in the analysed population (p<0.05). However, when compared between cases and control; there was no significant association between PAX9 SNP (rs8004560) with Class II skeletal base malocclusion (p=0.56, OR=0.71; 95% CI=0.225-2.246). The distribution of genotype frequency in both groups were consistent with HWE (p>0.05). Although no genetic association between PAX9 SNP (rs8004560) with Class II skeletal base malocclusion was observed, significant difference in allele frequency observed might provide some indication in the involvement of PAX9 polymorphism in Class II skeletal base malocclusion contributed by retrognathic mandible. Further research utilising larger sample size will be required in order to determine the role of PAX9 gene in the aetiology of Class II skeletal base malocclusion observed in the local Malaysian population.